Avaliação de náusea e êmese em pacientes sob quimioterapia em uma Unidade de Alta Complexidade Saúde de Vitória da Conquista/BA (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Nausea and emesis assessment in patients undergoing chemotherapy at an oncological unit in Vitória da Conquista/BA, Brazil